Pelatihan Pengelolaan Limbah Organik Rumah Tangga Menjadi Eco Enzyme Di Kelurahan Tiakar, Payakumbuh - Winny Alna Marlina; Devi Yulia Rahmi; Fatma Poni Mardiah; Nur Ari Sufiawan; Bintang Rizky Abdullah Majo Saibah (Warta Pengabdian Andalas, 2025)
Waste is still a problem throughout Indonesia, especially in Payakumbuh, West Sumatera. Every day, humans produce a large amount of organic and inorganic waste. This illustrates the need to utilize waste in Payakumbuh City, particularly in Tikar Village. Eco enzymes are useful for processing organic waste, especially fruit waste such as fruit peels and vegetable waste. Vegetable and fruit waste can be an alternative material for eco-enzyme production, reducing alcohol from fermented kitchen waste. The community is in high demand for eco enzyme due to its effectiveness in reducing waste, particularly when produced on a large scale, and its numerous benefits. The purpose this activity to manage the people to process the organic wastes into eco enzyme to create a clean environment. The location this activity was hold in office of Tiakar Regency in east Payakumbuh, Payakumbuh City, West Sumatera. The activity results show that training on processing vegetable and fruit waste into Eco Enzyme can reduce organic waste in Tiakar Village, Payakumbuh, by making Eco Enzyme cleaning fluid or disinfectant.